Effectiveness of NBF Gingival Gel use for treatment of patients with chronic catarrhal gingivitis - T. A. Petrushanko; T. N. Moshel; O. V. Hancho; I. Yu. Popovich; T. D. Bubliy; N. A. Bobrova (Zaporožskij Medicinskij Žurnal)
Aim. The purpose of our study was to evaluate the efficacy of NBF Gingival Gel in patients with chronic catarrhal gingivitis.